Lyric Poetry and Solitude in "Monolog" by Sulaiman Djaya and "Situ Lembang" by Dian Haridiana - Sutikno, Eka Ugi (Serat: Journal of Literary & Cultural Studies, 2024)
Many people write about his solitude in plain words, so the content is brief. Unfortunately, writing solitude in the form of literary works, especially poetry, is longer than done in conversation. Even ‘Monolog’ by Sulaiman Djaya and ‘Situ Lembang’ by Dian Haridiana display loneliness through narrative poetry. This article will discuss solitude as anonymity, creativity, inner peace, intimacy, problem-solving, self-discovery, spirituality, loneliness, and distraction in the two lyric poetry works above and how the lyric poetry impacts the story inside. Therefore, the quantitative method of description becomes the appropriate choice for analysis. The argument is that solitude is the intimacy of the subject to gain peace and independence.